Manajemen Pembelajaran Era Pandemi Covid-19 (Studi di SMP Negeri 2 dan SMK 7 Kota Bengkulu) - Danim, Sudarwan (Yayasan Sembilan Pemuda Indonesia, 2022)
This research was conducted in order to examine the function of learning management theory and practice in the era of the Covid-19 pandemic, including general policies, implementation, planning, evaluation, and quality assurance of learning when schools were fully closed and partially opened. This qualitative approach with a descriptive method research was conducted in SMP Negeri 2 and SMK Negeri 7 Bengkulu City by involving the principal of SMP Negeri 2 and SMK Negeri 7 Bengkulu City 1 person each and 20 teachers each as research informants. The data were collected using interviews and participant observation. Analytical technique of Miles and Huberman (1989) was used to obtain research results consisting of data reduction activities, data display, and conclusions or data verification. For the validity and reliability of this research, triangulation was carried out, both data, methods, sources, and theories. The results of the study show that the general policies set by schools to administer learning during the Covid-19 pandemic era follow the rules set by the central and regional governments. The principal initiates micro policies related to the implementation of the duties and functions of teachers and the ease of student learning processes.